GAMBARAN PENGETAHUAN PERTOLONGAN PERTAMA ASMA PADA PENDERITA ASMA DI DESA JUBEL KECAMATAN SUGIO KABUPATEN LAMONGAN - Attoriq, Habib Minhaj; Maghfiroh, Isni Lailatul; Maghfuroh, Lilis (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p11, 2023)
Knowledge is very influential in providing first aid to asthma sufferers. Lack of knowledge about asthma can lead to inappropriate asthma first aid measures in the Jubel Village community. Asthma first aid that is done properly can prevent exacerbations and death in asthmatics before getting help from health workers. The purpose of this study was to determine the knowledge of asthma sufferers about asthma first aid. Descriptive research design was used on 46 patients who were taken by consecutive sampling. This research was conducted in Jubel Village, Sugio District, Lamongan Regency in March 2023. Data were collected with an asthma first aid knowledge questionnaire containing knowledge about asthma disease, knowledge about asthma emergency signs, and knowledge about asthma first aid. The results showed that the knowledge of patients in Jubel Village, Sugio Subdistrict, Lamongan Regency about asthma first aid are mostly in the sufficient category (37%), almost half in the good category (34,8%), and almost a small portion in the poor category (28,3%). Knowledge of each indicator obtained knowledge of asthma disease with an average value of 70,38 in the moderate category, knowledge of asthma emergency signs with an average value of 72,83 in the moderate category, knowledge of asthma first aid with an average value of 64,40 in the moderate category.